2015
DOI: 10.1371/journal.pone.0128269
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Activated Peripheral Blood Memory B Cells in Rheumatoid Arthritis, Impact of B Cell Depletion Therapy, and Biomarkers of Response

Abstract: Although B cell depletion therapy (BCDT) is effective in a subset of rheumatoid arthritis (RA) patients, both mechanisms and biomarkers of response are poorly defined. Here we characterized abnormalities in B cell populations in RA and the impact of BCDT in order to elucidate B cell roles in the disease and response biomarkers. In active RA patients both CD27+IgD- switched memory (SM) and CD27-IgD- double negative memory (DN) peripheral blood B cells contained significantly higher fractions of CD95+ and CD21- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 54 publications
9
96
1
5
Order By: Relevance
“…To our knowledge, there is only one report of human antigen-specific MBCs surviving in the spleen after rituximab depletion (14). Several mechanisms underlying the persistence of B cells in tissues have been proposed, including resistance of activated B cells to rituximab-mediated depletion (61,63), effect of Fc glycosylation on rituximab and its resulting interaction with Fc receptors on accessory cells (64), the inflammatory or cytokine milieu allowing for B cells to survive (65,66), or possibly the inability of rituximab to fully access tissues to deplete B cells (67). It is also possible that CD20 expression is downregulated in B cells residing in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only one report of human antigen-specific MBCs surviving in the spleen after rituximab depletion (14). Several mechanisms underlying the persistence of B cells in tissues have been proposed, including resistance of activated B cells to rituximab-mediated depletion (61,63), effect of Fc glycosylation on rituximab and its resulting interaction with Fc receptors on accessory cells (64), the inflammatory or cytokine milieu allowing for B cells to survive (65,66), or possibly the inability of rituximab to fully access tissues to deplete B cells (67). It is also possible that CD20 expression is downregulated in B cells residing in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only memory B cells express SASP markers, especially the terminally differentiated B cell subset (CD19+IgD− CD27−), called late-memory/exhausted-memory, tissuelike, or double negative, which of all B cell subsets is the most pro-inflammatory. This subset has been reported to be increased in the blood of healthy elderly individuals 85,90 and in patients with autoimmune 96101 and infectious diseases, 102104 suggesting that, in a favorable inflammatory microenvironment, these cells may expand in vivo in the presence of autoantigens or pathogen-derived antigens, leading to the production of pathogenic (autoimmune) or protective antibodies, respectively.…”
Section: Predictors Of Optimal Vaccine Responsesmentioning
confidence: 99%
“…Indeed, this break in tolerance could involve both B cell intrinsic and extrinsic mechanisms. Furthermore the rapid return of memory B cells in the periphery following B cell depletion is a strong indicator of poor response to therapy [1], and further emphasizes the importance of studying the development of autoreactive B cells in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Although MS was historically thought to be driven by T cells [44], evidence for the importance of B cells in MS produced a shift in this perspective [25, 26]. The efficacy of B cell depletion therapy (BCDT) [40, 50], the prevalence of B cells in type II MS lesions [61], and the inverse correlation between memory B cell repopulation and benefit from BCDT [1]all support the hypothesis that B cells play a central role in pathogenesis [25, 26]. …”
Section: Introductionmentioning
confidence: 99%